Predicting lysine requirements using protein and lipid accretion curves for growing-finishing barrows - M De La Llata; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1999)
A total of240 growing-finishing barrows (75 to 260 lb) were used to model accretion rates and the lysine:calorie ratio requirement based on lipid and protein content data obtained with a real-time ultrasound. Barrows were fed eight different diets consisting of four increasing lysine:calorie ratios and two levels of fat (0 and 6%). The modeled accretion rates effectively predicted the differences between treatments in agreement with the actual data. The modeled lysine:calorie ratio requirement accurately predicted the lysine:calorie ratios that maximized growth, evaluated by either the predicted or the actual data. Lipid and protein deposition rates were used to effectively model feed intake when pigs were fed close to their requirement.; Swine Day, Manhattan, KS, November 18, 1999
Keywords: Swine day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 841; Swine; Real-time ultrasound; Lipid accretion; Protein accretion; Lysine:calorie ratio; Fat; Lysine; Finishing pigs